2002
DOI: 10.1021/jf020396t
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Shallot (Allium ascalonicum Hort.)

Abstract: An extensive phytochemical analysis of the polar extracts from bulbs of shallot, Allium ascalonicum Hort., led to the isolation of two new furostanol saponins, named ascalonicoside A1/A2 (1a/1b) and ascalonicoside B (4), respectively, along with compounds 2a and 2b, most likely extraction artifacts. On the basis of 2D NMR and mass spectrometry data, the structures of the novel compounds were elucidated as furost-5(6)-en-3beta,22alpha-diol 1beta-O-beta-D-galactopyranosyl 26-O-[alpha-L-rhamnopyranosyl-(1-->2)-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 15 publications
(42 reference statements)
7
90
0
4
Order By: Relevance
“…Differences in latitude may account for the differences in day length, light quality, UV radiation, and temperature. However, in agreement with the results of this research, it has been reported that shallots produce higher levels of flavonoids than bulb onions (Fattorusso et al, 2002;Leighton et al, 1992). In fact, shallots from Indonesia, which were cultivated near the equator and exposed to high UV radiation, produced the highest levels of flavonoids.…”
Section: Discussionsupporting
confidence: 92%
“…Differences in latitude may account for the differences in day length, light quality, UV radiation, and temperature. However, in agreement with the results of this research, it has been reported that shallots produce higher levels of flavonoids than bulb onions (Fattorusso et al, 2002;Leighton et al, 1992). In fact, shallots from Indonesia, which were cultivated near the equator and exposed to high UV radiation, produced the highest levels of flavonoids.…”
Section: Discussionsupporting
confidence: 92%
“…The axial-axial couplings H-3/H-4 and H-4/H-5, and the axialequatorial relationship between H-2 and H-3 as the resonances of C-3 and C-5 led to the determination of a L-rhamnose unit with -configuration. 11,12 The nature of the sugar moiety for both the compounds was deduced from the 1D ROESY and HMBC spectra, in which two sequences could be observed. The proposed sequences are confirmed after obtaining the 1 H NMR of minor aliquots from the chromatographic process with different intensities of anomeric signals.…”
Section: Resultsmentioning
confidence: 99%
“…3 -7 With regard to the saponin constituents of the Allium ascalonicum L., some steroidal saponins have been reported. 8 Further phytochemical analysis of the A. ascalonicum L. with attention to the steroidal glycoside constituents led to the isolation of two new furostanol saponins and two known furostanol saponins, dichotomin 9 and parisaponin I. 10 This paper reports the isolation and structural determination of two new furostanol saponins, compounds 1 and 2 ( Fig.…”
Section: Introductionmentioning
confidence: 96%